The Esperanto movement in the Dutch East Indies and Indonesia - Goes, Heidi (Wacana, Journal of the Humanities of Indonesia, 2015)
The Esperanto movement in Indonesia has grown in the past five years from being almost non-existent to having a national association with several clubs. One might therefore assume that the Esperanto movement in Indonesia is a totally recent phenomenon. However, already at the beginning of the twentieth century there were Esperantists in the territory of today's Indonesia. Between the two World Wars the movement was active: periodicals and books were published, courses held, and clubs and associations established. As a result of the Second World War this vigorous movement collapsed, but following independence the movement reflourished under the guidance of the Minangkabau journalist and feminist Rangkajo Chailan Sjamsoe Datoe Toemenggoeng. In November 1962 Datoe Toemenggoeng unfortunately passed away, and soon afterward the Esperanto movement again collapsed. Research reveals that this repeated disappearance of the movement was due not only to the death of this leader, but mostly to political factors.